OPTIMIZATION OF SURGICAL MANAGEMENT IN OBESE PATIENTS WITH INCISIONAL HERNIAS (Multidisciplinary Journal of Science and Technology, 2025)
The purpose of the scientific study is improve, optimize the results of operations performed in patients with "hanging abdomen" syndrome due to abdominal (ventral) hernia and obesity. In 153 patients treated in VKTTTM I-surgery department, the results of the operations of patients with abdominal wall hernia and obesity were analyzed into 2 groups. In the first group, 76 (control group) patients with obesity and ventral hernia performed a hernia-cutting procedure, in which surgical intervention on the" hanging " Corine was not performed; the main group (II group) was studied as a result of 77 patients undergoing resection of pannikulis, abdominoplasty and cut-off of the ventral hernia. Conclusion weight loss was found to be a positive result of the implementation of the reduction of the subcutaneous fat layer in the case of the abdomen (II, III levels of the paniculus) "hanging" along with the cutting of the ventral hernia, alloprotizing in patients, when as a result of the disease of obesity and the occurrence of the ventral hernia, along with the.